2017
DOI: 10.1515/pralin-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Neural Machine Translation Attention and Confidence

Abstract: In this article, we describe a tool for visualizing the output and attention weights of neural machine translation systems and for estimating confidence about the output based on the attention.Our aim is to help researchers and developers better understand the behaviour of their NMT systems without the need for any reference translations. Our tool includes command line and web-based interfaces that allow to systematically evaluate translation outputs from various engines and experiments. We also present a web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Estimating the confidence or quality of the output of MT systems (Ueffing and Ney, 2007;Specia et al, 2009;Bach et al, 2011;Salehi et al, 2014;Rikters and Fishel, 2017;Kepler et al, 2019) is important for enabling downstream applications such as post-editing and interactive MT to better cope with translation mistakes. While existing methods rely on external models to estimate confidence, our approach leverages model uncertainty to derive confidence measures.…”
Section: Confidence Estimationmentioning
confidence: 99%
“…Estimating the confidence or quality of the output of MT systems (Ueffing and Ney, 2007;Specia et al, 2009;Bach et al, 2011;Salehi et al, 2014;Rikters and Fishel, 2017;Kepler et al, 2019) is important for enabling downstream applications such as post-editing and interactive MT to better cope with translation mistakes. While existing methods rely on external models to estimate confidence, our approach leverages model uncertainty to derive confidence measures.…”
Section: Confidence Estimationmentioning
confidence: 99%
“…Other NN-based algorithms explore internal information from neural models as an indicator of translation quality. They rely on the entropy of attention weights in RNN-based NMT systems [23,35]. However, attention-based indicators perform competitively only when combined with other QE features in a supervised framework.…”
Section: Related Workmentioning
confidence: 99%
“…Stejně jako v městském autobuse či tramvaji. For inspecting the NMT attention alignments, we developed a tool (Rikters et al, 2017a) that takes data produced by Neural Monkey as input and produces a soft alignment visualization by connecting words and subword units (Sennrich et al, 2016b) as shown in Figure 5, which shows an example translation with two systems for En → Cs. Here it is clear that in the baseline alignment no attention goes to the word "městě" or the subword units "autobu@@" and "se" when translating "city".…”
Section: Referencementioning
confidence: 99%
“…To outperform the baselines, we explored 4 areas for improvements -1) filtering backtranslated data; 2) named entity forcing; 3) hybrid system combination; and 4) NMTspecific post-processing. The section is based on the paper of Rikters et al (2017a).…”
Section: Simple System Combination Using Neural Network Attentionmentioning
confidence: 99%